Lecture-recital: Bis repetita placent: C. P. E. Bach, W. A. Mozart, and the Sonata with Varied Reprises - Beghin, Tom (2024)
Annual Conference of the American Musicological Society 2024, Chicago (IL, US)
Abstract:This lecture-recital, featuring Tom Beghin on fortepiano, picks up on a suggestion that did not materialize. In October 1775, Leopold Mozart inquired of publisher Breitkopf in Leipzig whether the latter might like to print keyboard sonatas by his son “in the same manner as those of H: Philipp Carl Emanuel Bach mit veränderten Reprisen.” Irving (1998), Levin (2019) and others have proposed a link between Leopold’s offered works and Wolfgang Amadeus Mozart’s recently completed “Munich” Sonatas, K. 279–84 (1774–75). What might Mozart’s Six Sonatas with Varied Reprises have looked like? Reversely, what in Mozart’s score made Leopold think of a possible publication à la Bach?Using Bach’s Sechs Sonaten mit veränderten Reprisen Wq. 50 (1760) as a guide, Beghin extends a widely documented mid-eighteenth-century practice of embellishing repeats to the actual rewriting of Mozart’s reprises. Reprise here applies to either of the two sections of a sonata-form movement that are to be repeated. The expectation of such a repeat is crucial for our performing and listening to a “varied [repeat of a] reprise” in a rhetorical or pre-organicist paradigm (Broyles 1980; Bonds 1991; Beghin 2015).That Bach’s printed opus was meant to demonstrate how “one tends to vary the allegros with 2 reprises the second time around” (Bach, 1753) raises the stakes for our engagement with Mozart, who left us with fine examples of embellishing slow movements but whose fast movements in particular leave us guessing as to how he would have handled such an exercise. The idea here is to build on studies of Mozart as improviser (from Levin 1992/2003 to Bandy 2022/2023) but also to commit to a fully written-out, entirely publishable text. While Bach claimed to have invented a new genre “for the use and benefit” of the amateur, our challenge is to apply similar principles to what in Mozart’s household were known as “the difficult sonatas,” removing all repeat signs and replacing these with varied reprises.This lecture-recital proceeds in three parts. First, it contextualizes the larger issue of “repeat” in the German intellectual-artistic world of 1760–70, asking whether the truism of bis repetita placent (“things that are repeated please”) applied to performing (“one repeats to please more”) or listening (“something being so good that it is worth repeating”). The two, it will be suggested, were interconnected (Junker 1779, Sulzer 1776). Repeats offered musicians the “opportunity” (Quantz 1752) to engage in variation, and constantly applying varietas to one’s style or delivery—retaining the listener’s attention—was the hallmark of a professional, whether orator or musician.Second, turning to Wq. 50 and its preface, one must acknowledge the paradox in Bach’s gambit, which was to open a professional practice to the amateur. Promising “complete freedom regardless of one’s disposition,” Bach’s experimental format—a continuous script that may be read without having to “ask others to write variations” and “memorizing these with great difficulty”—certainly makes for stylistically inventive playing, where one may apply Bach’s own recently published rules of “good delivery” (Versuch, 1753). “Freedom,” however, does not come to mind when performing off his repeat-sign-less score. The absence of repeat signs—as visual anchoring points—come at a great loss of a player’s voluntas, or the rhetorical intent to either take it “from the top” or re-launch one’s energies toward the next reprise, which normally is accompanied by the not-to-be-missed gesture of turning the page. Yet, even if separated from its usual material-performative environment, “starting over, with variation” remains the musical message in Bach’s opus.Third, can we apply Bach’s strategies and solutions to Mozart? Here sections will select be selected from K. 279–284, looking for cues in his scores, and the event will end with a performance of a complete sonata, along with the projecting of a newly created score on screen.Abstract:This lecture-recital, featuring Tom Beghin on fortepiano, picks up on a suggestion that did not materialize. In October 1775, Leopold Mozart inquired of publisher Breitkopf in Leipzig whether the latter might like to print keyboard sonatas by his son “in the same manner as those of H: Philipp Carl Emanuel Bach mit veränderten Reprisen.” Irving (1998), Levin (2019) and others have proposed a link between Leopold’s offered works and Wolfgang Amadeus Mozart’s recently completed “Munich” Sonatas, K. 279–84 (1774–75). What might Mozart’s Six Sonatas with Varied Reprises have looked like? Reversely, what in Mozart’s score made Leopold think of a possible publication à la Bach?Using Bach’s Sechs Sonaten mit veränderten Reprisen Wq. 50 (1760) as a guide, Beghin extends a widely documented mid-eighteenth-century practice of embellishing repeats to the actual rewriting of Mozart’s reprises. Reprise here applies to either of the two sections of a sonata-form movement that are to be repeated. The expectation of such a repeat is crucial for our performing and listening to a “varied [repeat of a] reprise” in a rhetorical or pre-organicist paradigm (Broyles 1980; Bonds 1991; Beghin 2015).That Bach’s printed opus was meant to demonstrate how “one tends to vary the allegros with 2 reprises the second time around” (Bach, 1753) raises the stakes for our engagement with Mozart, who left us with fine examples of embellishing slow movements but whose fast movements in particular leave us guessing as to how he would have handled such an exercise. The idea here is to build on studies of Mozart as improviser (from Levin 1992/2003 to Bandy 2022/2023) but also to commit to a fully written-out, entirely publishable text. While Bach claimed to have invented a new genre “for the use and benefit” of the amateur, our challenge is to apply similar principles to what in Mozart’s household were known as “the difficult sonatas,” removing all repeat signs and replacing these with varied reprises.This lecture-recital proceeds in three parts. First, it contextualizes the larger issue of “repeat” in the German intellectual-artistic world of 1760–70, asking whether the truism of bis repetita placent (“things that are repeated please”) applied to performing (“one repeats to please more”) or listening (“something being so good that it is worth repeating”). The two, it will be suggested, were interconnected (Junker 1779, Sulzer 1776). Repeats offered musicians the “opportunity” (Quantz 1752) to engage in variation, and constantly applying varietas to one’s style or delivery—retaining the listener’s attention—was the hallmark of a professional, whether orator or musician.Second, turning to Wq. 50 and its preface, one must acknowledge the paradox in Bach’s gambit, which was to open a professional practice to the amateur. Promising “complete freedom regardless of one’s disposition,” Bach’s experimental format—a continuous script that may be read without having to “ask others to write variations” and “memorizing these with great difficulty”—certainly makes for stylistically inventive playing, where one may apply Bach’s own recently published rules of “good delivery” (Versuch, 1753). “Freedom,” however, does not come to mind when performing off his repeat-sign-less score. The absence of repeat signs—as visual anchoring points—come at a great loss of a player’s voluntas, or the rhetorical intent to either take it “from the top” or re-launch one’s energies toward the next reprise, which normally is accompanied by the not-to-be-missed gesture of turning the page. Yet, even if separated from its usual material-performative environment, “starting over, with variation” remains the musical message in Bach’s opus.Third, can we apply Bach’s strategies and solutions to Mozart? Here sections will select be selected from K. 279–284, looking for cues in his scores, and the event will end with a performance of a complete sonata, along with the projecting of a newly created score on screen.
FRIS
1
Keywords: Declassifying the Classics: Rhetoric, Technology, and Performance, 1750-1850